(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2023)
This article focuses on the importance of artificial intelligence in the labor market and its impact. The author describes the ability of artificial intelligence to affect several sectors and professions in the economy, the improvement and expansion of tasks due to automation of jobs, and the positive or negative impact of artificial intelligence on wages and labor productivity.